Preoperative Percutaneous Nerve Mapping of the Mandibular Marginal Branch of the Facial Nerve. Issue 2 (March 2015) - Lin, Bo; Lu, Xuguang; Shan, Xiaofeng; Zhang, Lei; Cai, Zhigang
<x xml:space="preserve">Abstract</x> Objective In this study, we introduce a reliable method for mapping the location of the mandibular marginal branch of the facial nerve. The utility of preoperative percutaneous mandibular marginal branch mapping and continuous intraoperative nerve monitoring during operation with a submandibular approach is reported. Materials and Methods The mapping technique was performed in 40 patients. Electromyography surface electrodes were placed on the orbicularis oris muscles. A modified bipolar probe with an adjustable distance between the 2 tips was used to apply surface stimulation at a frequency of 1 Hz to 2 Hz. The stimulating current most frequently used was 5.0 mA to 5.5 mA. By moving the electrode at right angles across the suspected path of the nerve around the marginal border of the mandible, 4 to 5 points were marked and connected, where the orbicularis oris contracted and the action potential was evoked. After general anesthesia, the mapping path was verified using needle electrodes with different needle-to-nerve distances. Results The nerve could be mapped preoperatively in all patients and were protected in 39 patients. The thresholds of the needle electrode on the mapping path were at or below 0.5 mA, verifying the accuracy of mapping. Conclusions Preoperative percutaneous nerve mapping was a precise method of identifying the location of the nerve and could protect the nerve from accidental injury.